2018
DOI: 10.1016/j.jsha.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of successful medical education of caregivers of children with congenital heart diseases

Abstract: Of children who had CHD, around 42.5% were males aged 5.65 ± 3.99 years and 37.3% had ventral septal defect, 14.4% had atrial septal defectand 19.5% had a complex CHD. Study results showed that 83.3% of caregivers were aware of the correct diagnosis and 64.2% had good understanding of the nature and effect of the disease. Frequently explained disease dimensions were impact on child's growth (65.8%), complications (57.5%), and outcomes (55.0%). Least frequently explained dimensions were those related to infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…emphasized the role of providing necessary information to caregivers by health professionals. [ 26 ] In accordance with the present results, previous studies have demonstrated that in today's society, the Internet as a high-capacity tool enables people to access health information;[ 27 ] however, this information probably does not satisfy them. [ 28 ]…”
Section: Discussionsupporting
confidence: 91%
“…emphasized the role of providing necessary information to caregivers by health professionals. [ 26 ] In accordance with the present results, previous studies have demonstrated that in today's society, the Internet as a high-capacity tool enables people to access health information;[ 27 ] however, this information probably does not satisfy them. [ 28 ]…”
Section: Discussionsupporting
confidence: 91%
“…Regarding ease of use, content, design and utility the app was described as a tool that enhanced data recording and communication with the medical team. Azhar 14 found similar results that indicated that even communication process and caregivers' skills were improved by using app tools and other technological devices.…”
Section: Discussionmentioning
confidence: 71%
“…In another survey published in 2014 Knöchelmann et al examined the maternal knowledge about infective endocarditis for children with CHD and concluded that education-efforts should be focused on mothers of children requiring IE prophylaxis (38). In Azhar et al found that only about 40% of caregivers received general information about IE and only one third or less could explain risk factors, symptoms and prophylaxis of IE (39). Since many patients with CHD receive anticoagulants or anti-plateletaggregation drugs, some high vascularity sites for piercings like tongue or penis should be avoided.…”
Section: Special Considerations For Patients With Chdmentioning
confidence: 99%